The Opportunities and challenges in socioenvironmental and corporate governance practices: Company B: Socio-environmental and corporate governance practices: Company B (Gestão & Regionalidade, 2025)
In recent decades, the population's production and consumption patterns have contributed to the worsening of the environmental and social crisis, due to the lack of commitment to sustainability, especially in the business sector. In this context, the concept of "Company B" emerges, which brings together corporate organizations that seek to solve socio-environmental problems in parallel with the development of their activities as a private entity. The purpose of this article is to analyze opportunities and challenges of institutions certified as "Company B". The methodology is based on document analysis of data from the "Company B" platform. As a result: several Brazilian companies are recognized in this segment (eg Natura, Aoka Tours, Granato). This movement is growing and can create new market opportunities and change in the behavior of consumers of these products, but there are still many doubts from companies regarding regulatory aspects of the market that make it difficult for a greater number of organizations to enter this segment.
Keywords: Corporate sustainability; Socioenvironmental responsability; B moviment; Low carbon economy